2018
DOI: 10.1002/adfm.201801398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thickness on Contact Issues for Pinning Effect in Black Phosphorus Field‐Effect Transistors

Abstract: Metal/semiconductor contact is a significant constraint in short-channel field effect transistors (FETs) comprising black phosphorus (BP) and other 2D semiconductors. Due to the pinning effect at metal/2D semiconductor interface, the Schottky barrier usually does not follow the Schottky-Mott rule, resulting in thickness-dependent FET performance. In this work, the Schottky barrier in BP FETs is investigated via theory calculation and electrical measurement. A simple metal/BP contact model is presented based up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 47 publications
3
47
1
Order By: Relevance
“…45 The presence of Fermi level pinning has already been suggested and studied theoretically for few-layer bP, 46 and it has been as well investigated experimentally. 32 What is observed for bP 32 Fermi level pinning. 47,48 Since in our sample processing we introduced an oxygen plasma step, this could have modified the surface state density, changing the conditions at the interface.…”
Section: Contact Resistancementioning
confidence: 82%
See 1 more Smart Citation
“…45 The presence of Fermi level pinning has already been suggested and studied theoretically for few-layer bP, 46 and it has been as well investigated experimentally. 32 What is observed for bP 32 Fermi level pinning. 47,48 Since in our sample processing we introduced an oxygen plasma step, this could have modified the surface state density, changing the conditions at the interface.…”
Section: Contact Resistancementioning
confidence: 82%
“…Despite the interest in this topic, experimentally, up to now, just few studies on the contact resistance to bP were reported. 15,15,[30][31][32][33] Among them, a big focus is on the transition between unipolar and ambipolar behavior in bP. 15,31 Even if several metals were inspected, it is difficult to extract a consistent picture, given also the differences in sample fabrication techniques among the various studies, but most of all because of the high reactivity of bP, whose uncontrolled oxidation, hard to prevent, introduces a large uncertainty in the observed behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The opposite phenomenon about the relationship of the I on / I off versus temperature was observed in Figure d. To further quantify the Schottky barrier between Cr/Te, it can be deduced by the equation Ids = AAT2expqnormalΦkBT[]1normalexpqVdsknormalBT where I ds is the current through the device, Φ is the Schottky barrier, q is the magnitude of the electron charge, T is the temperature, and V ds is 1 V. When V g is above V FB , thermally assisted tunneling current becomes dominating which leads to the nonlinear behavior . By contrast, the thermionic emission current predominates the current.…”
Section: Resultsmentioning
confidence: 98%
“…The device is p-type with an intrinsic resistance ~300 Ω. We note that the on/off ratio for the range of gate voltages shown is only ~15, which is typical of thicker BP FETs due to the relatively high conductance of the naturally doped bulk crystal and the small out-of-plane screening length 28,45,46 .…”
mentioning
confidence: 91%